Increased both cortical activation and functional connectivity after transcranial direct current stimulation in patients with post-stroke: A functional near-infrared spectroscopy study - Yang, Caihong; Zhang, Tingyu; Huang, Kaiqi; Xiong, Menghui; Liu, Huiyu; Wang, Pu; Zhang, Yan (Frontiers in Psychiatry, 2022)
Background: Previous studies have shown that cognitive impairment is common after stroke. Transcranial direct current stimulation (tDCS) is a promising tool for rehabilitating cognitive impairment. This study aimed to investigate the effects of tDCS on the rehabilitation of cognitive impairment in patients with stroke. Methods: Twenty-two mild-moderate poststroke patients with cognitive impairments were treated with 14 tDCS sessions. A total of 14 healthy individuals were included in the control group. Cognitive function was assessed using the Mini-Mental State Exam (MMSE) and the Montreal Cognitive Assessment (MoCA). Cortical activation was assessed using functional Near-Infrared Spectroscopy (fNIRS) during the Verbal Fluency Task (VFT). Results: The cognitive function of stroke patients, as assessed by the MMSE and MoCA scores, was lower than that of healthy individuals but improved after tDCS. The cortical activation of stroke patients was lower than that of healthy individuals in the left superior temporal cortex (lSTC), right superior temporal cortex (rSTC), right dorsolateral prefrontal cortex (rDLPFC), right ventrolateral prefrontal cortex (rVLPFC), and left ventrolateral prefrontal cortex (lVLPFC) cortical regions. Cortical activation increased in the lSTC cortex after tDCS. The functional connectivity (FC) between the cerebral hemispheres of stroke patients was lower than that of healthy individuals but increased after tDCS. Conclusion: The cognitive and brain functions of mild-to-moderate stroke patients were damaged but recovered to a degree after tDCS stimulation. Increased cortical activation and increased FC between the bilateral cerebral hemispheres measured by fNIRS are promising biomarkers to assess the effectiveness of tDCS in stroke.